The first commercially approved efficacious cryptosporidium vaccine protecting New-Born calves from severe diarrhea - Marina Timmermans; Willem Hubers; Dianne Schroer; Koen Gevers; Ruud PAM Segers; Ron Niessen; Mark H van Roosmalen (Veterinary Vaccine, 2024)
Neonatal calf diarrhea (NCD) is an important cause of morbidity and mortality in calves. Four major pathogens, including Enterotoxigenic Escherichia coli (ETEC), bovine rotavirus (BRV), bovine coronavirus (BCV), and Cryptosporidium spp., are associated with NCD, with Cryptosporidium parvum (C. parvum) recognized as a major contributor. Despite various treatment options available, there is no effective vaccine for bovine cryptosporidiosis yet. In this study, recombinantly expressed C. parvum gp40 was evaluated as a candidate vaccine in pregnant animals. The vaccine was administered to pregnant cows during the last trimester of their pregnancy resulting in highly statistically significantly increased anti-gp40 antibody titers. The resulting anti-gp40 antibodies were transmitted to the calves via colostrum. Both suckling (n = 29; test:14, control:15) and non-suckling (n = 16; 8 per group) calves were challenged with live C. parvum oocysts. The calves that received the colostrum from gp40 vaccinated cows showed a highly statistically significant improvement in health (p < 0.0001), reduced incidence (p < 0.0001), and duration of severe diarrhea (p < 0.001) and increased weight gain in suckling calves (p < 0.0001). This study demonstrates that immune bovine colostrum, induced by immunization of late-gestation cows with C. parvum gp40, provided substantial protection to calves against cryptosporidiosis. These findings suggest that the gp40 vaccine has potential for preventing outbreaks of neonatal diarrhea associated with cryptosporidiosis in calves, thereby improving animal welfare and performance.